The Legal Responsibility of the Air Carrier for the Damages Caused by Terrorist Operations - Ahmed Jabbar Hadi Al-Allaq (Indonesian Journal of Law and Economics Review, 2026)
General Background: Global security faces escalating threats from terrorism, particularly targeting air transport systems which constitute critical infrastructure for international commerce and communication. Specific Background: Terrorist incidents in aviation have proliferated, ranging from aircraft hijacking to in-flight sabotage, creating unprecedented challenges for determining civil liability frameworks under international conventions such as the 1999 Montreal Convention. Knowledge Gap: Despite extensive international legislation, ambiguity persists regarding the precise legal basis and extent of air carrier responsibility for damages resulting from terrorist acts during air transportation operations. Aims: This study examines the civil liability of air carriers for terrorism-related damages, analyzing international conventions and judicial precedents to determine accountability parameters throughout the air transport process. Results: The research establishes that carrier responsibility extends to terrorist incidents when adequate preventive security measures are not implemented, with liability encompassing both pre-incident negligence and post-incident failure to mitigate consequences, irrespective of foreign cause defenses. Novelty: The study adopts an expanded interpretation of "air accidents" that encompasses terrorism as carrier-related incidents rather than external events, thereby broadening the scope of compensable damages beyond traditional aviation accident frameworks. Implications: These findings mandate stricter carrier obligations for passenger protection, ensuring compensation accessibility for terrorism victims while promoting enhanced aviation security measures globally.Keywords : Air Carrier Liability, International Terrorism, Civil Aviation Security, Montreal Convention, Passenger CompensationHighlight : Air carriers bear responsibility when failing to implement necessary terrorist prevention measures. Montreal Convention 1999 combines fault-based and objective liability for passenger protection balance. Terrorist incidents qualify as air accidents warranting carrier compensation regardless of perpetrator prosecution.